Patch Pd para Nih-Nik de Chico Mello - Silva, Gabriel Montechiari (Revista Vórtex, 2014)
This Pure Data patch was commissioned by the Ensemble Nih-Nik for the premier of the homonymous 1993 piece by Brazilian composer Chico Mello at the SiMN 2014 + matrix14 on tour festival (Curitiba, Brazil).